Solvent dependent triplet state delocalization in a co-facial porphyrin heterodimer. Issue 48 (6th December 2022) - Ciuti, Susanna; Toninato, Jacopo; Barbon, Antonio; Zarrabi, Niloofar; Poddutoori, Prashanth K.; van der Est, Art; Di Valentin, Marilena
Abstract : The excited triplet state of a cofacial aluminum(iii ) porphyrin–phosphorus(v ) porphyrin heterodimer is investigated using transient EPR spectroscopy and quantum chemical calculations. Abstract : The excited triplet state of a cofacial aluminum(iii ) porphyrin–phosphorus(v ) porphyrin heterodimer is investigated using transient EPR spectroscopy and quantum chemical calculations. In the dimer, the two porphyrins are bound covalently to each other via a μ-oxo bond between the Al and P centres, which results in strong electronic interaction between the porphyrin rings. The spin polarized transient EPR spectrum of the dimer is narrower than the spectra of the constituent monomers and the magnitude of the zero-field splitting parameter D is solvent dependent, decreasing as the polarity of the solvent increases. The quantum chemical calculations show that the spin density of the triplet state is delocalized over both porphyrins, while magnetophotoselection measurements reveal that, in contrast to the value of D, the relative orientation of the ZFS axes and the excitation transition dipole moments are not solvent dependent. Together the results indicate that triplet state wavefunction is delocalized over both porphyrins and has a modest degree of charge-transfer character that increases with increasing solvent polarity. The sign of the spin polarization pattern of the dimer triplet state is opposite to that of the monomers. The positive sign of D predicted for the monomers and dimer by the quantum chemical calculations implies that the different signs of the spin polarization patterns is a result of a difference in the spin selectivity of the intersystem crossing.